STEM-BASED LEARNING DESIGN: ENHANCING STUDENTS’ SCIENTIFIC AND ENGINEERING LITERACY THROUGH A GREEN REFRIGERANT BOX IN ELEMENTARY SCHOOLS - Pinkan Amita Tri Prasasti; Octarina Hidayatus Sholikhah; Naif Mastoor Alsulami (JURNAL EDUSCIENCE, 2026)
Purpose –This study aims to explore how a STEM-based learning design integrated with the engineering design process in enhancing elementary school students’ scientific and engineering literacy through the Green Refrigerant Box innovation in elementary schools.Methodology – A mixed-methods sequential explanatory design was employed. The quantitative phase used a quasi-experimental non-equivalent control group design involving 122 fifth-grade students from four elementary schools. The experimental group received STEM-based learning integrated with the engineering design process, while the control group followed regular instruction without STEM-based learning. Data were collected using scientific and engineering literacy tests and analyzed using N-gain and ANCOVA, with effect sizes reported using partial eta squared (η²ₚ). The qualitative phase involved observations, interviews, and documentation, analyzed through thematic analysis to support the quantitative results.Findings – The experimental group showed higher improvement in scientific literacy (N-gain = 0.63, moderate–high) than the control group (0.36, moderate), with a significant effect (F = 58.72, p < 0.001, η²ₚ = 0.33). Engineering literacy also improved more in the experimental group (0.55, moderate) compared to the control group (0.27, low–moderate), with a significant effect (F = 46.35, p < 0.001, η²ₚ = 0.28). Qualitative findings revealed shifts toward mechanistic reasoning, improved data interpretation, and stronger connections between scientific concepts and real-world contexts, along with more systematic design thinkingContribution – This study highlights the complementary relationship between scientific and engineering literacy, where science informs design decisions and engineering reinforces conceptual understanding, and offers empirical insights into STEM-based learning in elementary education